The Romanian Internal Public Audit System – An X-Ray Analysis of Audit Compartment Activities - Adelina DUMITRESCU PECULEA (Revista de Management Comparat International)
Closely following the Romania’s EU-Integration, the public administration began a drastic reform process of all its systems, including internal public audit. In this regard, even right after 1989, a connection to European governance mechanisms and the implementation of European best practices were sought. Thus, building an efficient and sustainable public administration migrated over time from intention to necessity and lately to priority of all development strategies. For implementing such mechanism, clear and transparent decision processes, a good management of available resources, an adequate institutional and administrative structure and standards centered on public interest promotion are necessary. This paper presents an X-Ray like image of the public audit system in Romania, for the implementation of an efficient management in public entities as part of public sector good governance. The sustainable development of public administration is in need of an audit system consolidation, based on specialists contributing to reaching objectives by improving information flows and efficient risk management.